Reder evaluation system and the strategic plan of a confessional private institution - Villar Guevara, Miluska (2019)
This article aims to describe the level of compliance of the strategic plan through the REDER evaluation system of a private confessional institution, from 2017-2019. The methodology used is descriptive, non-experimental, cross-sectional, and elaborated under a quantitative approach. When interpreting the results statistically, the SPSS 24 Software was used for descriptive analysis of frequency and cross-tabulations. An instrument of 26 items was applied, divided into 5 dimensions, which was administered to a population of 45 people in the administration. It was found that 40% of the total study population perceives very high and notable levels of compliance; however, 35.6% registered non-compliance with these parameters. It is concluded that the level of compliance with the strategic plan through the REDER evaluation system is below the average standards; which translates to a point of improvement in regards to the patterns of a strategic plan.